Effects of different drying methods on smears of canine blood and effusion fluid - De Witte,Fiamma G.; Hebrard,Aimee; Grimes,Carolyn N.; Owens,Kristin; Schaefer,Deanna M.; Zhu,Xiaojuan; Fry,Michael M. (PeerJ, 2020)
Background Glass slide preparations from a variety of specimens (blood, masses, effusions) are commonly made as part of the diagnostic work-up, however the effects of various drying methods in veterinary practice and diagnostic laboratory settings is not clear. Objective Compare the effects of four drying methods on results of microscopic examination of canine blood smears and direct smears of pleural or peritoneal effusion fluid. Methods Twelve canine blood samples (6 from healthy dogs, 6 from sick dogs) and 6 canine peritoneal or pleural effusion samples. Four smears were prepared from each of the 18 samples and dried using the following methods: air-dry, hair dryer with or without heat, and heat block at 58 °C. Observers, blinded to the drying method, independently reviewed the slides microscopically, using a scoring system to evaluate cell morphology and (for blood smears) echinocyte numbers; scoring results were analyzed statistically. Results For blood smears, several comparisons showed more adverse effects on morphology using the heat block method than for one or more other drying methods. For effusion fluid smears, RBCs dried with the heat block or air-dry methods had more poorly preserved morphology than RBCs dried by the hair dryer method without heat. Conclusions and clinical relevance The results (1) indicate that different drying methods had a significant effect, (2) support using a hair dryer without heat for both blood smears and effusion fluid smears, and (3) discourage using a 58 °C heat block.
Keywords: Canine; Smears; Slides; Blood; Effusion; Drying methods; Hairdryer